Introduction: Spectral Thinking. Issue 1 (26th April 2018) - CROSS, JONATHAN
Abstract: Can we any longer usefully speak of spectral music, beyond a very particular moment in Paris in the 1970s? Though the label still has a currency, the validity of the term has long been disputed even by its key practitioners. Gérard Grisey preferred to speak of liminal music, music on a threshold, and of spectralism as an attitude rather than a set of techniques. Yet a shared curiosity about the inner life of sounds, stimulated by an engagement with technology, certainly enabled a radical rethinking and renewal of how music could speak. Spectral thinking enabled composers to re-engage with time, with listening, with memory. Through this spectral node flowed all other kinds of music, which flowered in all sorts of new and varied directions. A heightened awareness of the properties of sound prompted new modes of musical thought and expression. Spectralism also represented a renewal of what might be understood more broadly as modernist thinking in the music of the later twentieth century. Spectral thinking – rather than merely the science of the spectrum of sound – acknowledges the importance for so-called spectral music of a wider set of concerns that engage with time, space, listening, nature, and society.